Infective Etiologies in Patients with Bilateral Congenital Cataract - Qadir, Abdul; Naeem, Saquib; Khan, Taimoor Ashraf; Khan, Umair Naeem; Liaqat, Talha; Butt, Waqas Rahim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of positive Toxoplasma, Rubella, Cytomegalovirus, Herpes Simplex virus and Syphilis serology in patients with bilateral congenital cataract and their correlation with different type of cataracts and age groups. Study Design: Cross sectional study. Place and Duration of Study: Department of Pediatric Ophthalmology and Strabismus, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from May to Dec 2022. Methodology: Data was collected by a single investigator on Microsoft Excel sheet including patient’s age, gender, mode of delivery, consanguinity of parents, and type of congenital cataract, results of TORCH Screening and Presence or absence of amblyopia. TORCHS screening comprised of serum IgM and IgG levels for Toxoplasmosis, Rubella, Cytomegalovirus, Herpes Simplex virus and Syphilis. Results: A total of 134 patients reported to our institute with bilateral congenital cataract during the study period. Out of them 56 patients had positive results of TORCH screening (41.7%) Out of total 56 patients with bilateral congenital cataract testing positive for TORCH, 30(53.6%) were male while 26(46.4%) were female. Age range was from 1-17 months (9.2±4.2 months).Lamellar cataract was the most common cataract type in our study sample 16(28.6%). Conclusion: In patients with bilateral congenital cataract positive TORCHS serology was most frequent. Serum Rubella IgM followed by Rubella IgG was positive in most cases. Most common age of presentation in our study was from 4-7 months. Furthermore, lamellar cataract followed by nuclear cataract was the commonest cataract type.